EFFECT OF FORENSIC AUDITING ON THE FINANCIAL PERFORMANCE OF QUOTED FOOD AND BEVERAGE FIRMS IN NIGERIA - Ahmed Oluwatobi Adekunle (J-MACC, 2025)
The number of financial and economic fraud cases have increased recently, but fraud is a dynamic phenomenon, and new ways to mislead people, businesses and society at large. The aim of this study is to determine the effect of forensic auditing on the financial performance of quoted food and beverage firms in Nigeria. The research design employed in this study is ex-post facto research. ex-post facto research determines the cause-effect relationship among variables. The study applies secondary data, the statistical tool used to test the hypothesis was STATA 13 statistical software, using coefficient of correlation which is a good measure of relationship between two variables. The study revealed that forensic auditing has a positive and statistically significant effect on ROA, ROE, and EPS of food and beverage firms quoted on the floor of Nigerian stock exchange at 5% level of significance. The study recommends that to boost profitability, management of food and beverage companies should prioritize and improve the use of forensic audit data. Secondly, if fraud is discovered, the investigation should be carried out by qualified professionals like Professional Forensic Auditors and fraud examiners, and if there is evidence of fraud, appropriate disciplinary action should be taken in compliance with the public service rules. The investigation should also follow the correct forensic audit procedures